Thrombotic burden, D-dimer levels and complete compression ultrasound for diagnosis of acute symptomatic deep vein thrombosis of the lower limbs. Issue 213 (May 2022) - Cosmi, Benilde; Legnani, Cristina; Cini, Michela; Tomba, Sara; Migliaccio, Ludovica; Borgese, Laura; Sartori, Michelangelo; Palareti, Gualtiero
Abstract: Background: Diagnostic algorithms for deep vein thrombosis (DVT) include D-dimer for its high negative predictive value, thus reducing the need for imaging. Small thrombi may be associated with low D-dimer levels, increasing false negatives. Aim: To assess the sensitivity and thus the false negative rates of standard and age-adjusted D-dimer cut offs for isolated distal DVT (IDDVT) in outpatients. Materials and methods: We enrolled consecutive outpatients with suspected DVT of the lower limbs referring to our vascular emergency department from 2009 to 2018. Patients underwent D-dimer testing (STA, Stago, cut-off: 500 μg/L), pretest clinical probability (PTP) evaluation and complete compression ultrasonography. Follow-up was 3 months. Results: Among 3948 patients (M:1554–39%, median age 69), 486 proximal DVTs (12.3%) and 348 IDDVTs (8.8%) were diagnosed. Median D-dimer was higher in proximal than IDDVT (3960 vs 1400 μgr/L; p = 0.001). The false negative rate of the standard D-dimer cut-off was 2% (95%CI: 0.8–3.2%) for proximal DVT and 14.7% (95% CI: 11–81%) for IDDVT. The false negative rate of the age-adjusted cut-off was 4.9% (3–7%) for proximal DVT and 19.5% (95% CI: 15.4–24.7%) for IDDVT. Conclusions: Small calf thrombi are associated with low D-dimer levels, and age-adjusted D-dimer may be below the cut-off more frequently in subjects with IDDVT than standard cut-off D-dimer, although such D-dimer levels might exclude IDDVT that require treatment. Highlights: DVT diagnostic algorithms employ D-dimer for its high negative predictive value, thus reducing the need for imaging Small thrombi can be associated with low D-dimer levels, possibly thus reducing the yield of diagnostic algorithms D-dimer levels correlate with the extent of DVT, and small calf thrombi are associated with low D dimer levels D-dimer levels correlate with the extent of DVT, and small calf thrombi are associated with low D dimer levels. Age-adjusted D-dimer are below the cut-off more frequently in subjects with IDDVT than standard cut-off D-dimer